2004
DOI: 10.1590/s1020-49892004000300002
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of antibodies against rubella virus in pregnant women in Haiti

Abstract: This study is an important first step in addressing the issue of prevalence of rubella virus infection among Haitian women and in dealing with the still-underrecognized public health problem of congenital rubella syndrome in Haiti. We recommend additional research that uses randomized sampling and includes a significant proportion of women from rural areas of the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The rubella virus plays a significant role in the occurrence of abortion Desinor et al, 2004;Palihawadana et al, 2003). The data presented in this study has found that, the seroprevalance of Rubella virus was in agreement with those reported in other African countries in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The rubella virus plays a significant role in the occurrence of abortion Desinor et al, 2004;Palihawadana et al, 2003). The data presented in this study has found that, the seroprevalance of Rubella virus was in agreement with those reported in other African countries in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the vaccination program was put in place in Cameroon less than five years ago. WHO statistics show that this virus is present in Cameroon with 83, 159, 58, and 126 confirmed cases in 2004, 2005, 2006, and 2007 respectively [13,14]. These cases were first suspected cases of measles which turned out negative and instead tested positive for Rubella.…”
Section: Introductionmentioning
confidence: 99%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%